(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT : Information System Management of the National Land policy issued by the government to help communities in the rapid completion of the maintenance of land given the land is something lasting and useful for humans. Implementation of the policy of the National Land Management Information System is still not going well, so this research to answer the question of how the policy implementation of the National Land Management Information System. In this study, the researchers limited the Model Policy of Edward III, communications, resources and attitude.and researchers also see from the quality factor of services that exist in the land office Manado. This study uses descriptive qualitatively approach through in-depth interviews to 10 informants, observation and search for additional documents in the form of a list of guidelines for the interview, a tape recorder and stationery. The results showed that the overall implementation of the national land management information system has not done well. Keywords: Policy Land Management Information System (SIMTANAS) Communication, Resources, attitude and quality of service.